O ser e o fazer : os intelectuais e o povo no Recife dos anos 1960 - SILVA, Bianca Nogueira da (2010)
1960 consists of an effervescent and controversial chapters in the history of the city of Recife in its early republic. Several policy initiatives and cultural activities are held in urban upper chamber, as the New Cinema, Theatre Street, unions, the Movement for Basic Education, Neighborhood Associations, the Cultural Squares etc. Cultural movements that use dramas and everyday relationships as raw material for their works and thereby build a differentiated perception of the concept of popular culture and education, as well as its political role in society. Among these organizations, the experience of creation of the Popular Culture Movement - MCP (1960-1964) is taken here as the main object of this work, the focus chosen for analysis is the role played by its main creators: the intellectuals, as well as its main manufacturing: the people. The MCP in this sense, it constitutes in our view as a rich vantage point from Recife, in the first half of the 1960s, not only in its cultural aspects, but also from the standpoint of social and relationship between the so-called intellectuals and the public. Thus, the main goal of our work is to provide a historiographical contribution as regards the analysis of historical categories "people" and "intellectuals" and of their enterprises in the construction and development of a project of democratic society for the city of Recife of the early 1960s. To this end, we use the journalistic discourses, official documents of the Municipality of Recife and the State Legislative Assembly and the status of the MCP, as one of the fields of performance and ideological formation of these intellectuals on the people. Backed by an Enlightenment ideal, where through popular education to social development was made possible, these intellectuals have launched a series of efforts in trying to raise culturally the people, and are forced to retreat with the coup civil-military on the 1st of April 1964.